Multi-objective optimal design of permanent magnet synchronous motor - Cvetkovski, Goga; Petkovska, Lidija (IEEE, 2016)
In this paper a genetic algorithm based optimal design of a permanent magnet synchronous motor (PMSM) is proposed. This approach employs a genetic algorithm (GA) technique as a search tool for optimal design solution of a PMSM based on the value of the objective function. The sum of the efficiency of the motor and the inverse value of the permanent magnet total weight is selected as a multi-objective function. An overall comparative analysis of the optimisation parameters and the values of certain important motor parameter of the prototype model and the optimal solution motor is presented.
Keywords: Optimization, genetic algorithm, multi-objective optimization, permanent magnet synchronous motor, finite element method.